Studies on the surface chemistry based on competitive adsorption of NOx-SO2 onto a KOH impregnated activated carbon in excess O-2 - Lee, YW; Park, JW; Yun, JH; Lee, JH; Choi, DK (AMER CHEMICAL SOC, 2002)
This study identifies surface chemistry characteristics based on competitive behavior in the simultaneous adsorption behavior of NOx (NO rich) and SO2 using KOH impregnated activated carbon (K-IAC) in excess O-2. The NOx and SO2 adsorption on K-IAC occurred mainly through the acid-base reaction. The high surface area with many pores of activated carbon acted as storage places of oxide crystal produced from NOx and SO2 adsorption, KOH, an impregnant, provided the selective adsorption sites to NOx and SO2, enabling simultaneous adsorption. However, larger amounts Of SO2, with higher adsorption affinity to K-IAC compared to NOx, were adsorbed in a NOx/SO2 coexistent atmosphere. Oxygen was chemisorbed to K-IAC, which enhanced the selective adsorptivity for NO. In binary-component adsorption of NOx and SO2 on K-IAC, oxide crystals such as KNOx (x = 2,3) and K2SOx (x = 3,4) were dominantly formed through two different adsorption mechanisms by chemical reaction. Depending on the extent that oxide crystals blocked pores, compositions of oxide crystals were distributed differently according to depth.
Keywords: NO REDUCTION; SULFUR-DIOXIDE; REMOVAL; COAL; MECHANISM; COKE; CHAR; SO2; GAS